Optimalisasi Kemampuan Membaca Siswa SMP Muhammadiyah Kwandang: Analisis Faktor dan Solusi Efektif - Robiyana Lasomba; Ayu Agrini S. Antung; Dewiski Lamusu; Ismiyati Gani; Ulfa Zakaria (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Reading ability is one of the basic skills that is important to support the student learning process. However, in SMP Muhammadiyah Kwandang, it was found that 10 out of 47 students had difficulty reading which had an impact on their learning outcomes. This study aims to analyze the factors causing reading difficulties and offer effective solutions. The approach used was qualitative with a case study method. The results showed that reading difficulties were caused by psychological, socio-economic, and external factors. Physical factors such as visual and hearing impairments were not found to be the main cause. The proposed solutions include reading guidance programs, innovative teaching methods such as the use of letter cards and reading together, and collaboration between teachers, students, and parents. The implementation of this strategy succeeded in significantly improving students' reading abilities.